Literasi Digital dalam Pendidikan Nonformal Berbasis Komunitas: Systematic Literature Review tentang Pembelajaran Orang Dewasa, Kesenjangan Digital, dan Pemberdayaan - A. Hasdiansyah (Prodi PGSD Unsultra, 2026)
This article synthesizes literature on digital literacy in community-based non-formal education, focusing on adult learning, the digital divide, and empowerment. The study employed a systematic literature review guided by PRISMA 2020. Searches were conducted through Scopus-oriented sources, Google Scholar, Garuda, Sinta, DOAJ, and ERIC for publications from 2019 to 2026. Of 38 records screened, 32 articles were included in the core thematic synthesis. The analysis used four lenses: adult learning, community-based strategies, the digital divide, and empowerment. The findings show that digital literacy in non-formal education is not merely a matter of technical device mastery, but a social learning process shaped by practical needs, mentoring, peer tutoring, learning communities, and institutional support. The digital divide appears in access, skills, confidence, autonomy of use, and the ability to gain tangible benefits. In Indonesia, community learning centers, villages, youth communities, women groups, and micro-enterprise groups can become strategic spaces for linking digital literacy with socio-economic empowerment.